Genetic variation in reproductive timing in a long‐lived herbaceous perennial. Issue 11 (13th November 2022) - Reed, Will J.; Ison, Jennifer L.; Waananen, Amy; Shaw, Frank H.; Wagenius, Stuart; Shaw, Ruth G.
Abstract: Premise: Reproductive fitness of individual plants depends on the timing of flowering, especially in mate‐limited populations, such as those in fragmented habitats. When flowering time traits are associated with differential reproductive success, the narrow‐sense heritability ( h 2 ) of traits will determine how rapidly trait means evolve in response to selection. Heritability of flowering time is documented in many annual plants. However, estimating h 2 of flowering time in perennials presents additional methodological challenges, often including paternity assignment and trait expression over multiple years. Methods: We evaluated the h 2 of onset and duration of flowering using offspring–midparent regressions and restricted maximum likelihood methods in an experimental population of an iterocarpic, perennial, herbaceous plant, Echinacea angustifolia, growing in natural conditions. We assessed the flowering time of the parental cohort in 2005 and 2006; the offspring in 2014 through 2017. We also examined the effects of the paternity assignment from Cervus and MasterBayes on estimates of h 2 . Results: We found substantial h 2 for onset and duration of flowering. We also observed variation in estimates among years. The most reliable estimates for both traits fell in the range of 0.1–0.17. We found evidence of a genotype by year interaction for onset of flowering and strong evidence that genotypes are consistent in their duration of flowering across years. Conclusions: Substantial heritabilities in this population imply the capacity for a response to natural selection, while also suggesting the potential for differential contributions to adaptive evolution among seasons.